2004
DOI: 10.1111/j.1479-828x.2004.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Case series of a single centre's treatment of ovulatory infertility with clomiphene citrate and intrauterine insemination in 2002

Abstract: The present paper reports a single department's retrospective case series of all clomiphene citrate (CC) combined with intrauterine insemination (IUI) treatment cycles for ovulatory infertility performed during 2002. Thirty-eight couples with unexplained, endometriosis, male or unilateral tubal factor infertility had undergone 71 cycles of CC and IUI. The clinical and ongoing cycle pregnancy rates were 20 and 17%, respectively. Seven percent of the clinical pregnancies were multiple pregnancies, with all multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2010
2010
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…The miscarriage rate at our center was 29% which was higher than that reported in other studies (20.96% by Guzick et al). The multiple pregnancy rate was only 4.3% in our study as compared to 7% reported by Costello et al 9 probably because a significant number of patients in our study with twin pregnancy miscarried. The ongoing pregnancy rate in our center was 5.6% which is comparable to the 6.7% ongoing pregnancy rate reported by Steures et al 4 .…”
Section: Discussioncontrasting
confidence: 87%
“…The miscarriage rate at our center was 29% which was higher than that reported in other studies (20.96% by Guzick et al). The multiple pregnancy rate was only 4.3% in our study as compared to 7% reported by Costello et al 9 probably because a significant number of patients in our study with twin pregnancy miscarried. The ongoing pregnancy rate in our center was 5.6% which is comparable to the 6.7% ongoing pregnancy rate reported by Steures et al 4 .…”
Section: Discussioncontrasting
confidence: 87%
“…If all of the inclusion criteria were verified within the 12 months prior to initiation of participation, women were included. Women were excluded from the study when the inclusion criteria were not met, or if hormone supplementation (including clomiphene citrate13), in vitro fertilization or intrauterine insemination treatments were undertaken during the 6-month study period. Those women with minimal/mild endometriosis were included in the study, as were women over the age of 35 (age typically classified as the cutoff for high-risk pregnancies to develop).…”
Section: Methodsmentioning
confidence: 99%
“…Despite this negative effect, CC usually leads to pregnancy in approximately one-third of patients with ovulatory dysfunction undergoing a course of therapy (7). Unfortunately, there is a significant multiple pregnancy rate (PR), varying from 6%-11% (2,8,9).…”
mentioning
confidence: 97%